The clinical value of indirect immunofluorescence for screening anti-rods and rings antibodies: A retrospective study of two centers in China - Meng, Jingjing; Yang, Guoxiang; Li, Siting; Luo, Yueming; Bai, Yina; Deng, Chuiwen; Song, Ning; Li, Mengtao; Zeng, Xiaofeng; Hu, Chaojun (Frontiers in Immunology, 2022)
Objective: To investigate the distribution and clinical significance of the rods and rings (RR) pattern in various diseases. Methods: A total of 169,891 patients in Peking Union Medical College Hospital (PUMCH) and 29,458 patients in Inner Mongolia People's Hospital (IMPH) from January 2018 to December 2020 were included, and the results of ANA (antinuclear antibodies) and special antibodies were analyzed retrospectively. Results: The positive rates of ANA and RR patterns were 34.84%, 0.16% in PUMCH, and 44.73%, 0.23% in IMPH. Anti-RR antibodies mainly appear in adults (≥ 41 years), mostly of low or medium fluorescence titers. Isolated RR patterns were mostly presented (60.30% and 69.12%, respectively), and the RR pattern mixed with the speckled pattern was most commonly observed among patients having two or more patterns. The RR pattern existed in a variety of diseases including hepatitis C, AIDs, pulmonary diseases, nephropathy diseases, and even healthy people. The highest prevalence of the RR pattern was observed in hepatic diseases, such as hepatic dysfunction (0.79%), hepatic cirrhosis (1.05%), PBC (0.85%), and AIH (0.65%), etc. The positive rate of specific antibodies in RR pattern cases was 31.25%, and anti-Ro52 (27, 20.61%) was the most common target antibody. Conclusion: The RR pattern had a low prevalence in ANAs test samples and varied in different nationalities and regions. Except for hepatitis C, it could be observed in AIDs, pulmonary diseases, nephropathy, other hepatic diseases, and even healthy people, but the positive rate was slightly higher in hepatic diseases. Its mechanism of action and clinical relevance still need clarification.